Dva modela ženskega pravljičarstva na Slovenskem – pisateljice in pripovedovalkeTwo Models of Women Storytelling in Slovenia – Women Writers and Women Performers of Fairy Tales - Mileva Blažić, Milena (Studia mythologica Slavica, 2016)
<span style="line-height: 115%; font-family: 'Helvetica','sans-serif'; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">In the article are presented Slovenian women fairy tale writers who were included in the streams of fairy tale writing in the middle of the 19th century, when Josipina Turnograjska published the fairy tale “Rožmanova Lenčica” (Rožman’s Lenčica) in 1853. This is much later than the start of European women fairy tale writing, which has its roots in the late medieval period with the trobairitz, and continued in the 16th century. After that the new stream of women fairy tale writers developed with the preciosite in the 17th century. The author researches development of women fairy tale writing in Slovenia and classifies their creation of fairy tales in two main models: writing literary fairy tales and storytelling or performing folktales. Lately, among Slovenian women, writing contemporary fairy tales is also popular.